2018
DOI: 10.5812/aapm.83610
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Bypass Alone Does Not Cause Postoperative Cognitive Dysfunction Following Open Heart Surgery

Abstract: BackgroundPostoperative cognitive dysfunction (POCD) is commonly observed following cardiac surgery. The utilization of cardiopulmonary bypass (CPB) is associated with many possible mechanisms to cause POCD. However, there is no evidence confirming that CPB alone is the cause of POCD.ObjectivesThe current study aimed at evaluating several factors suspected to cause POCD following cardiac surgery in Cipto Mangunkusumo Hospital, Jakarta, Indonesia.MethodsThe current prospective cohort study was conducted on 54 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Moreover, there was no significant difference in demographic characteristics, cardiovascular risk factors, and perioperative factors between the POCD and non-POCD group in our current study. Consistently, Soenarto et al (2018) have reported that the duration of cross-clamp, the duration of cardiopulmonary bypass, diabetes mellitus, and education level were not significantly different in the POCD and non-POCD group. However, Vacas et al (2013) reported that the duration of surgery and anesthesia and BMI would be the potential risk factors for POCD, which might be due to the different populations and neurocognitive testing modalities.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, there was no significant difference in demographic characteristics, cardiovascular risk factors, and perioperative factors between the POCD and non-POCD group in our current study. Consistently, Soenarto et al (2018) have reported that the duration of cross-clamp, the duration of cardiopulmonary bypass, diabetes mellitus, and education level were not significantly different in the POCD and non-POCD group. However, Vacas et al (2013) reported that the duration of surgery and anesthesia and BMI would be the potential risk factors for POCD, which might be due to the different populations and neurocognitive testing modalities.…”
Section: Discussionsupporting
confidence: 64%
“…Incidence of POCD in this study was higher than in our previous study (56.4% vs. 40.7%) [4]. The oxygenation statuses in this study were maintained well during and after surgery, both in subjects with and without POCD.…”
Section: Discussioncontrasting
confidence: 54%
“…Globally, POCD prevalence can be as high as 40%, with that number rising to up to 50% following open-heart surgery. A 2017 study in our hospital showed that the prevalence of POCD following openheart surgery was 40.7% [4].…”
Section: Introductionmentioning
confidence: 85%
“…Neurocognitive dysfunction often occurs after cardiopulmonary bypass surgery 8 . Researchers have studied the absolute rSO 2 value and the decrease in the percentage of rSO 2 from baseline and have concluded that if a patientā€™s rSO 2 level decreases by more than 20% from baseline, the prognosis of neurocognitive function could be poor 9,10 .…”
Section: Introductionmentioning
confidence: 99%